Influence of concomitant meniscal allograft transplantation on midterm outcomes after osteochondral allograft transplantation: a comparative matched-pair analysis - Husen, Martin; Wang, Allen S.; Levy, Bruce A.; Saris, Daniël B.F.; Stuart, Michael J.; Krych, Aaron J. (The American journal of sports medicine, 2024)
Background: Osteochondral allograft transplantation (OCAT) is an accepted knee joint-preserving treatment strategy for focal osteochondral lesions that is often conducted in combination with meniscal allograft transplantation (MAT). Despite its frequent and simultaneous utilization, there remains a lack in the literature reporting on outcomes and failure rates after concomitant procedures. - Purpose: To determine (1) the midterm clinical success rate after OCAT+MAT in comparison with a matched-pair cohort undergoing isolated OCAT, (2) whether patient-specific and procedural variables influence the risk of failure, and (3) patient-reported outcome measures over time. - Study Design: Cohort study; Level of evidence, 3. - Methods: A single-center matched-pair cohort study was conducted investigating outcomes in patients who underwent OCAT of the medial or lateral femoral condyle with and without MAT between 2004 and 2020. Patients were matched 1:1 by age (±5 years), sex (male or female), body mass index (±5), and grouped Kellgren and Lawrence grade (grades 0-1 or 2-4). The minimum follow-up time was 2 years. Radiographic variables (International Cartilage Regeneration & Joint Preservation Society [ICRS] grade and Kellgren and Lawrence grade) were assessed preoperatively and at follow-up. Subjective patient-reported outcome measures (Lysholm score, Knee injury and Osteoarthritis Outcome Score [KOOS] including subscores, International Knee Documentation Committee [IKDC] score, and visual analog scale score) were collected preoperatively and at follow-up. Clinical failure was defined as revision surgery for graft failure or conversion to total knee arthroplasty. Patient-reported, clinical, and radiographic outcomes were compared between groups. - Results: In total, 66 patients (33 treated with isolated OCAT, 33 treated with OCAT+MAT; 57.6% male) with a mean age of 26.3 years (range, 18-62 years) were followed for a mean of 5.6 years (minimum, 2 years; range, 24-218 months). The 2 cohorts showed no difference in Kellgren and Lawrence grade postoperatively (P = .59). There was a significantly higher ICRS grade detected at follow-up in the OCAT+MAT group (2.81 ± 1.10) compared with the OCAT group (2.04 ± 0.96) (P < .05). There were no statistically significant differences between the groups regarding reoperation rate (OCAT: n = 6; OCAT+MAT: n = 13; P = .116), time to reoperation (OCAT: 46.67 ± 47.27 months vs OCAT+MAT: 28.08 ± 30.16 months; P = .061), and failure rate (OCAT: n = 4 [12.1%] vs OCAT+MAT: n = 5 [15.2%]; P = .66). In the OCAT+MAT group, an increase of tibial slope by 1° conferred a 1.65-fold increase in the hazard for failure over decreased slope (hazard ratio, 1.65; 95% CI, 1.10-2.50; P < .05). The overall survival rate was 86% at a mean follow-up of 5.6 years. Patient-reported outcome scores were significantly improved at the final follow-up compared with preoperative status. No significant differences were seen between groups with respect to subjective IKDC, Lysholm, Tegner, and KOOS results, except for the KOOS Symptoms subscale score, which was significantly higher in the OCAT+MAT group than in the OCAT group (mean difference, 14.6; P < .05) and did exceed the minimal clinically important difference threshold of 10.7. - Conclusion: Midterm results after isolated OCAT and OCAT+MAT show high rates of healing and sustainable subjective improvement of knee function and quality of life. However, it should be noted that the difference in reoperation rate and time to reoperation between the groups is arguably clinically important and that lack of statistical significance may be because of low power. These results imply that isolated OCAT is an efficient joint-preserving treatment that can be combined with MAT in well-selected patients with meniscal insufficiency without negative influence on global clinical outcomes.